3+6f=5f

Simple and best practice solution for 3+6f=5f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+6f=5f equation:


Simplifying
3 + 6f = 5f

Solving
3 + 6f = 5f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-5f' to each side of the equation.
3 + 6f + -5f = 5f + -5f

Combine like terms: 6f + -5f = 1f
3 + 1f = 5f + -5f

Combine like terms: 5f + -5f = 0
3 + 1f = 0

Add '-3' to each side of the equation.
3 + -3 + 1f = 0 + -3

Combine like terms: 3 + -3 = 0
0 + 1f = 0 + -3
1f = 0 + -3

Combine like terms: 0 + -3 = -3
1f = -3

Divide each side by '1'.
f = -3

Simplifying
f = -3

See similar equations:

| x^2+81x+81=0 | | 5b-10=10b | | -7j+10=-10-9j | | 2x+6x=-85+5 | | 2g=-16 | | -g=10g | | -10+6u=4u | | n+19=3 | | -1-3x=9x-13 | | -w+3-10w=4-10w | | -6q=-4q-10 | | 4X^1=50 | | -5s=-8s+9 | | .4x-y+6=0 | | 3n-8/2*6=6 | | 4m-8=3m | | 6+10z=-10+6z | | 4z=6z+8 | | 2j=j+9 | | X^2-6x-96=-130 | | -3f+10=-10+7f | | -3f+10=-10 | | -5b-6=-111 | | 7m=8+6m | | 92+87+88+x=270 | | -22+3=m-5 | | -2n=8+2n | | x^2+42x+360=0 | | 6r-6=3r | | -3v=-4v-10 | | 10+9u=10u | | 12p^2= |

Equations solver categories